On the Path to Regularity: Exploring the Individual Costs of Regularization among Ukrainian Ageing Domestic and Care Workers in Italy - Feyduk, Olena (Lidé města, 2016)
This study focuses on the paths to regularization of Ukrainian migrants in Italy. Qualitative in its method and relying on in-depth semi-structured interviews, it uncovers in depth the fragmentation of status and rights that the process of regularization often brings, focusing specifically on the individual costs of “becoming regular.” The study subsequently looks at the emerging compensating mechanisms and networks that are developed by migrants in place of institutional dead-ends. Legality and regularity in migration – often presented in policy and public debates as a black and white matter – are in practice a complex and lengthy process for migrating individuals. The study makes its contribution by examining how individual migrants often individually shoulder costs linked to regularization, utilizing a combination of formal and informal means to achieve it. Most importantly, the study’s contribution highlights the role of age, gender and type of employment on the paths to regularity; by looking at the experiences of ageing women providing care and domestic work in private homes in Bologna I explore how age and individual relations with their families back at home and at work affect the meaning of regularization for this category of migrants and influence their prospects of ageing.